Trichodinids (Ciliophora: Peritrichida) parasitic on gills of freshwater fishes, Carassius auratus and Aristichthys nobilis from China, with the description of Trichodina subtilihamata sp. nov. - Tang, Fahui; Zhao, Yuanjun; Tao, Yanfei (Zootaxa, 2007)
Five trichodinid ectoparasites (Ciliophora: Peritrichida) were isolated from two freshwater fishes, Carassius auratus and Aristichthys nobilis collected from Chongqing, China. Trichodina subtilihamata sp. nov. is described from the gills of Carassius auratus and characterized by a slender hooked blade. The other four species of trichodinids are: Trichodina mutabilis Kazubski & Migala, 1968, Trichodina uniforma Van As & Basson, 1989, Trichodina nigra Lom, 1960 and Trichodina kazubski Van As & Basson, 1989. Comparative descriptions, with photomicrographs and morphometric data, are presented of these trichodinids to establish locality records. Descriptions presented here were obtained by examinations of specimens prepared using the dry silver nitrate impregation and the methyl green-pyronin staining. Comparisons with closely related species are provided for the new species.